2013
DOI: 10.1248/bpb.b12-01021
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of Cholera Toxin B Subunit in Lactobacilli

Abstract: Lactic acid bacteria (LAB) are used in various fields, including in food and medical supplies. There has been a great deal of research into vaccine development using LAB as carriers due to their "generally recognized as safe" status. Cholera is an infectious disease that causes diarrhea due to cholera toxin (CT) produced by Vibrio cholerae. The pentameric cholera toxin B (CTB) subunit has no toxicity, and is used as an antigen in cholera vaccines and as a delivery molecule in vaccines to various diseases. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In contrast, Dertzbaugh and Cox reported that CTB can bind to nickel ions without a His-tag because of a specific histidine residue within its sequence [17]. However, we recently showed that the purification of rCTB with a His-tag from the culture supernatant of L. casei was 20 times more efficient than the purification of rCTB without a His-tag [5]. The GM1-ganglioside-binding activity of rCTB with a His-tag, secreted by L. casei , was similar to those of rCTB without a His-tag and native CT from V. cholerae [5].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, Dertzbaugh and Cox reported that CTB can bind to nickel ions without a His-tag because of a specific histidine residue within its sequence [17]. However, we recently showed that the purification of rCTB with a His-tag from the culture supernatant of L. casei was 20 times more efficient than the purification of rCTB without a His-tag [5]. The GM1-ganglioside-binding activity of rCTB with a His-tag, secreted by L. casei , was similar to those of rCTB without a His-tag and native CT from V. cholerae [5].…”
Section: Resultsmentioning
confidence: 99%
“…However, we recently showed that the purification of rCTB with a His-tag from the culture supernatant of L. casei was 20 times more efficient than the purification of rCTB without a His-tag [5]. The GM1-ganglioside-binding activity of rCTB with a His-tag, secreted by L. casei , was similar to those of rCTB without a His-tag and native CT from V. cholerae [5]. Therefore, to avoid any steric effects on the structure and GM1-ganglioside-binding activity of rCTB secreted by L. casei , we fused YVAD and the His-tag to the C-terminus of CTB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations